Impact of forestry on environment and human health: an evidence-based investigation - Addas, Abdullah (Frontiers in Public Health, 2023)
There is increasing interest in the health effects of the forest. Without active participation in forestry, conflicts between the various stakeholders are foreseeable. The impact of forests on human life is unforgettable, and everyone gets enormous benefits from trees and greenery. COVID-19 has caused many changes in human behaviour, which needs much attention. Environmental changes' impact is considered a better solution and influences human behaviour. Scientists around the globe are conducting research experiments on trees and the effect of forestry on human health, which is increasing in terms of social, ecological, and economic services. Trees provide full support to enhance the quality of life and minimize air pollution. Forests must be noticed to get benefits (e.g., carbon storage, fruits, human health considerations, economic benefits, and bio-diversity). This research aims to explain the area of forest and health from the perspective of Saudi Arabian forestry to develop strategic measures for the proactive design of this topic. The research entailed expert interviews with forestry representatives and a quantitative survey of medical students. Our findings show that implementing strategic measures such as establishing a forest and health improves health and eliminates air pollution. It shows many other establishment and planning strategies, such as the use of professional visitor monitoring, the development of product innovations, the use of digitalization and the development of integrated forest management.